Maintainability Allocation of EMUs Electric Traction Systems - SHAO Zhi-he; HE-zai; LIU Xue-quan (机车电传动)
System maintainability allocation method was expounded. Function diagram and mathematical model on maintainability for EMUs electric traction systems were established, and weighted method was used for the distribution. EMUs electric traction systems target allocation was analyzed, and the weak links in its maintainability design was identified, which provided reference and guidance for the design of EMUs electric traction systems repair element (fault detection and isolation, accessibility, convertibility, adjustment).